IoT based Smart Lighting System in an Auditorium - Mahandran, Indiran (Progress in Engineering Application and Technology, 2021)
Recent trends in industrial and home control systems have been witnessed with the evolution of automation technologies. Despite its modest beginning in past decades, automation has advanced from wired to wireless control over simple to complex control applications. With the existence of different types of automation systems, the process control nature has become progressed to provide higher productivity at a lower cost. IoT technologies can lift environmental pressure, increase operational efficiency, and improve building management, by allowing to distantly monitor and control facilities and collect actionable data on energy use, maintenance, and waste management. “Automation puts the people out of work” is a common misconception of automation. But the reason for turning the process of operation to be automated is to increase the productivity, quality, reduce manual checking, improve safety, reduce the production cost, and to be operator friendly. Nevertheless, public facilities such as an auditorium mainly use manual operation. This could be difficult to operate due to the large space unless a technician is available. Hence, designing a user-friendly device to control lighting without a control booth set could save time and energy. Lastly, having a smart lighting system can be easily customized to fit the mood of occasions.